Tempo Zawose - Gannibal, Lwiza (Lwiza Gannibal, 2020)
Bagamoyo, Tanzania, 2019. In an isolated village live members of the Zawose family. A family of artists who cultivate the musical heritage, handed down from generation to generation, of the Wagogo people, made up of a unique repertoire and handcrafted instruments.